The strength and stiffness of shear webs with round lightening holes having 45 degree flanges - Kuhn, Paul (National Advisory Committee for Aeronautics, 1942)
Tests were made of 18 shear webs with round lightening holes having 45 degree flanges. The purpose of the tests was to extend the range of a previous investigation to larger ratios of hole diameter to web depth and of web depth to web thickness. Simple empirical formulas are given for the strength and the stiffness of shear webs; these formulas incorporate the results of the previous investigation. Design charts are also given to facilitate the application of the results.
NACA Wartime Report L-323.
Originally issued as NACA as an Advance Restricted Report (December 1942).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Aluminum alloys -- Testing.; Holes.; Strength of materials.; Flanges.; Charts, diagrams, etc.; elektronické knihy; electronic books